Melvin Mencher's news reporting and writing - Mencher, Melvin (McGraw-Hill Higher Education, 2008)
More than a quarter of a million students have learned the craft and ethics of journalism from Melvin Mencher's News Reporting and Writing. This classic text shows students the fundamentals of reporting and writing and examines the values that direct and underline the practice of journalism. The new edition features current developments in all areas of reporting, discusses the use of stark photos, provides dozens of new Internet sources and demonstrates how journalists use them. Also included in the eleventh edition are guides for campaign and election coverage, reporting tips from Pulitzer Prize winners, and an examination of recent libel cases